2021
DOI: 10.1371/journal.pone.0254561
|View full text |Cite
|
Sign up to set email alerts
|

Basic emergency obstetric and newborn care service availability and readiness in Nepal: Analysis of the 2015 Nepal Health Facility Survey

Abstract: Background Achieving maternal and newborn related Sustainable Development Goals targets is challenging for Nepal, mainly due to poor quality of maternity services. In this context, we aim to assess the Basic Emergency Obstetric and Newborn Care (BEmONC) service availability and readiness in health facilities in Nepal by analyzing data from Nepal Health Facility Survey (NHFS), 2015. Methods We utilized cross-sectional data from the nationally representative NHFS, 2015. Service availability was measured by sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
4
13
1
Order By: Relevance
“…Factors associated with BEmONC service readiness. 1% in 2021 from 16.1% in 2015[15]. These findings also tally with the findings presented in Annual report of DoHS.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Factors associated with BEmONC service readiness. 1% in 2021 from 16.1% in 2015[15]. These findings also tally with the findings presented in Annual report of DoHS.…”
supporting
confidence: 91%
“…Facilities in Bagmati Province had higher BEmONC service readiness score (by 3.37 points, p-value=0.034). Unlike previous study [15], the BEmONC service readiness was better in rural area ( 2.76 points, p-value=0.008) which could be because higher proportion of health workers in rural area have been trained on BEmONC related services [12].…”
Section: Resultsmentioning
confidence: 60%
“…In contrast, health facilities of Karnali province had poor structural quality PLOS GLOBAL PUBLIC HEALTH perinatal services, which are likely to result in poor quality MNH services. These findings resonate with available evidence; for instance, past studies suggest that peripheral health facilities were poorly prepared for quality primary health services in Nepal [30][31][32], India [63], and Burkina Faso [64]. This is of concern as peripheral health facilities provide most routine ANC, childbirth PNC services [60].…”
Section: Plos Global Public Healthsupporting
confidence: 73%
“…Based on the information available in the dataset and previous studies [30][31][32], seven health facility level independent variables were selected, such as managing authority (Private, Public), facility types, provinces (province 1 -not named yet), Madhesh, Bagmati, Gandaki, Lumbini, Karnali, Sudurpaschim), mechanism of quality assurance (Yes, No), frequency of health facilities' management meeting (No, Sometimes, and Monthly), the existence of feedback collection system in health facilities (Yes, No), availability of external supervision of staff (Yes, No). In addition, Routine quality assurance activity was coded as "yes" for facilities reporting that it routinely carries out quality assurance activities (documentation of report or minutes of a quality assurance meeting, a supervisory checklist, a mortality review, or an audit of records or registers) and "No" for those without such quality assurance activities [28].…”
Section: Independent Variablesmentioning
confidence: 99%
“…We created a new independent variable, i.e., health facility capacity, which refers to the structural or input quality of a facility that provides a specific service. Studies reported that better input quality/ capacity of facilities could deliver better technical quality health services [29,[57][58][59][60]. Health facility capacity was created by conducting Principal Component Analysis (PCA) to generate composite-scale coefficients to reduce indicators to indices for application in comparative analyses of health facility readiness [61].…”
Section: Study Variablesmentioning
confidence: 99%